Bacteria-induced IMD-Relish-AMPs pathway activation in Chinese mitten crab. Issue 106 (November 2020) - Bai, Longwei; Zhou, Kaimin; Li, Hao; Qin, Yukai; Wang, Qun; Li, Weiwei
Abstract: The innate immune response is an important line of defense against invading pathogens in invertebrates. Signaling pathways, including the IMD pathway, play critical roles in the production of antimicrobial peptides (AMPs), which induce the transcription of immune effectors that protect against bacterial invasion. In the present study, the cDNA of IMD from Eriocheir sinensis was cloned (designated Es IMD) and shown to be significantly upregulated following Gram-positive and Gram-negative bacterial infection. In vivo and in vitro studies collectively suggested that both the Gram-negative bacterium Vibrio parahemolyticus and the Gram-positive bacteria Staphylococcus aureus and Bacillus subtilis elicit the translocation of Relish. Moreover, Es IMD positively regulated Es Relish translocation from the cytoplasm to the nucleus following stimulation with both Gram-positive and Gram-negative bacteria. Es Relish knockdown in hemocytes significantly suppressed AMPs' expression. Furthermore, both Lys-type and DAP-type peptidoglycan-containing bacteria activated the IMD pathway and elicited antibacterial responses in crab. Conclusively, these findings demonstrate that both Gram-positive and Gram-negative bacteria activate IMD signaling, via a mechanism that is distinct with that by which Gram-negative bacteria activate IMD signaling in Drosophila . These findings might pave the way for a better understanding of the innate immune system and the fundamental network of the IMD signaling pathway in crustacean. Highlights: Eriocheir sinensis IMD ( Es IMD) is upregulated by bacterial infection. Bacteria (Gram +/- ) induce nuclear translocation of Es Relish. Nuclear translocation of Es Relish is regulated by Es IMD. Bacteria (Gram +/- ) activate IMD signaling in E. sinensis.